International Capital Movements and the Theory of Tariffs and Trade - Jones, Ronald W. (Quarterly Journal of Economics, 1967)
I. Introduction, 1. — II. The model, 3. — III. Full optimization and complete specialization, 8. — IV. Full optimization and incomplete specialization, 10. — V. Optimal tax policy with free trade, 16. — VI. Optimal tariff policy with mobile capital, 23. — VII. Summary and conclusions, 31.